2017
DOI: 10.15640/ijmp.v5n1a3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Physicochemical Propertiesof Isosorbide Gel Composed of Xanthan Gum, Locust Bean Gum and Agar for Improving the Patient�s Adherence

Abstract: Isosorbide (ISB) has been widely used as a treatment for improving the endolymphatic hydrops of Meniere's disease. In general, ISB is used as a 70%(w/w) solution in medical treatments; however, ISB has a bitter taste,which reduces patient compliance. In recent years, jelly or gel formulations have been developed as "patient-friendly" and/or "patient-convenient" formulation. In this study, we attempted to develop various gel formulations of ISB to improve patient'sadherence. We used xanthan gum (XG), locust bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
0
0
1
Order By: Relevance
“…Cohesiveness refers to the mechanical textural attribute relating to the degree to which a food can be deformed before it breaks (Chen & Rosenthal, 2015). Kawano et al (2017) highlighted that cohesiveness is crucial for consumer acceptance across all age groups. The fortified pomegranate GC samples showed cohesiveness, ranging from 0.92 to 0.98 during storage, with no significant difference.…”
Section: Effect Of Ambient Storage On Texture Propertiesmentioning
confidence: 99%
“…Cohesiveness refers to the mechanical textural attribute relating to the degree to which a food can be deformed before it breaks (Chen & Rosenthal, 2015). Kawano et al (2017) highlighted that cohesiveness is crucial for consumer acceptance across all age groups. The fortified pomegranate GC samples showed cohesiveness, ranging from 0.92 to 0.98 during storage, with no significant difference.…”
Section: Effect Of Ambient Storage On Texture Propertiesmentioning
confidence: 99%
“…Previous research has shown that gelling agents such as alginate beads can effectively mask the bitter taste of Momordica charantia extract [62]. Other gelling agents, such as xantham gum, locust bean gum, and agar have been reported to reduce the bitterness of ambroxol hydrochloride [65]. The gelling agents will modify the overall texture of the jelly, masking the unpleasant taste of the extract and creating a smoother and more cohesive mouthfeel.…”
Section: E-tonguementioning
confidence: 99%
“…The gelling agents will modify the overall texture of the jelly, masking the unpleasant taste of the extract and creating a smoother and more cohesive mouthfeel. This can help to improve overall palatability [65].…”
Section: E-tonguementioning
confidence: 99%
See 1 more Smart Citation
“…Nilai ini merepresentasikan daya kohesif produk permen jeli. Permen jeli yang memiliki nilai kohesif rendah menandakan bahwa produk tersebut mudah untuk dikunyah sehingga memiliki korelasi positif terhadap daya terima produk permen jeli dan dapat dikonsumsi segala usia (Kawano et al 2017) termasuk anak-anak. Pada penelitian ini keseluruhan formula mempunya nilai cohesiveness antara 0,38 dan 0,81 yang sejalan dengan hasil penelitian Mutlu et al (2018).…”
Section: Cohesivenessunclassified